Chemical composition of the essential oils from cell culture of dendrobium parishii Rchb. F. - Jakaphun Julsrigival (2018)
This study identified the chemical composition of essential oils produced by cell culture of Dendrobium parishii Rchb. F. The cell cultures were established on Vacin and Went (VW) medium without plant growth regulator. The chemical compounds of essential oils were determined by Gas Chromatography/Mass Spectrometry (GC/MS) coupled with Head Space Solid Phase Micro-extraction (HS-SPME). Twenty-nine compounds of essential oils were identified. The main constituents were a-panasinsen (16.34%), hexadecanoic acid, ethyl ester (10.48%) and β-selinene (9.08%). Sesquiterpenes were the major constituents of the essential oils synthesized by cell culture of D. parishii Rchb. F. This research is the first to report on the composition of the essential oils obtained from this plant by cell culture as shown here, a promising technique for larger-scale and faster production of these essential oils. The chemical compounds identified may offer the potential for medicinal and cosmetic use.